Effect of malarial infection on haematological parameters in population near Thailand-Myanmar border - Manas Kotepui (2018)
Background: Malaria is a major mosquito-borne public health problem in Thailand with varied haematological consequences. The study sought to elucidate the haematological changes in people who suspected malaria infection and their possible predictive values of malaria infection. Methods. Haematological parameters of 4,985 patients, including 703 malaria-infected and 4,282 non-malaria infected, who admitted at Phop Phra Hospital, Tak Province, an area of malaria endemic transmission in Thailand during 2009 were evaluated. Results: The following parameters were significantly lower in malaria-infected patients; red blood cells (RBCs) count, haemoglobin (Hb), platelets count, white blood cells (WBCs) count, neutrophil, monocyte, lymphocyte and eosinophil counts, while mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), Mean corpuscular haemoglobin concentration (MCHC), neutrophil-lymphocyte ratio (NLR), and monocyte-lymphocyte ratio (MLR) were higher in comparison to non-malaria infected patients. Patients with platelet counts < 150,000/uL were 31.8 times (odds ratio) more likely to have a malaria infection. Thrombocytopenia was present in 84.9% of malaria-infected patients and was independent of age, gender and nationality (P value < 0.0001). Conclusion: Patients infected with malaria exhibited important changes in most of haematological parameters with low platelet, WBCs, and lymphocyte counts being the most important predictors of malaria infection. When used in combination with other clinical and microscopy methods, these parameters could improve malaria diagnosis and treatment. © 2014 Kotepui et al.; licensee BioMed Central Ltd.